Implementasi Program Banyuwangi Mengajar dalam Upaya Peningkatan Kualitas Pendidikan (Studi pada Dinas Pendidikan Kabupaten Banyuwangi) - Wanto, Alfi Haris; Syahbana, Arfi Ali (Jurnal Ilmiah Administrasi Publik, 2017)
Banyuwangi teaching program is implemented on the basis that schools in areas with difficult access levels (called Detas schools), lacked of teachers, so that the learning process not able to walk properly, the problem appears because of the moratorium on civil servants. In addition, the school's operational support funds too few, so it is impossible to add auxiliary teachers at the school because of the salary is too few. Therefore, in 2014 Department of Educational Banyuwangi Regency implement Banyuwangi teaching program to overcome the problem.Implementation of Banyuwangi teaching program in Banyuwangi Regency was conducted by Banyuwangi Teaching Team (Department of Educational Banyuwangi Regency) along with assigned volunteers to Detas schools. For maximum benefits, Department of Educational Banyuwangi Regency should be provide training to volunteers in order to have the provision when commissioned and the addition of the budget so it is capable of assigning many volunteers in schools Detas in Banyuwangi Regency.